Roles of social media in disseminating inheritance estate management information - Kamarudin, Mohd Khairy; Suhaimi, Mohd Hafizie; Nor Muhamad, Nasrul Hisyam; Mohd Noor, Sulaiman Shakib; Hehsan, Aminudin; Abu@Hussin, Mohd Fauzi; Ruskam, Aminuddin; Zulkifli, Abdul Halim; Muhamad Zain, Norhidayu (IAEME, 2018)
This study aims to identify the extent to which social media disseminates information related to inheritance estate management in Malaysia. It is a qualitative study using the thematic analysis. Samples of this research are Facebook ‘Pages’ with ‘likers’. There are four themes; ‘Organized activities’, “General information’, “Advertisement’ and “Call for feedback’. This study discovers that Facebook ‘Pages’ related to inheritance estate management do not emphasize much on organized activities and general information related to inheritance estate management. The ‘Pages’ also do not share information regularly and the time interval between a ‘Post’ to another one is long. This study recommends that owners of Facebook ‘Pages’ should update their information and activities frequently, and employ FB ads to provide information on the inheritance estate management.